2013
DOI: 10.3109/19396368.2013.772679
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional image analysis of the chromocenter in motile and immotile human sperm

Abstract: Chromosomes in human spermatozoa are arranged nonrandomly with the centromeres of non-homologous chromosomes forming a chromocenter. We have compared motile and immotile sperm populations in normozoospermic patients to determine if there is any dissimilarity in the formation of the chromocenter and the nuclear position of chromosome 17. Based on the differences between motile and immotile populations, we propose for the 'optimal' nuclear organization to be defined as containing 1 to 3 chromocenter(s) with cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 38 publications
4
44
0
Order By: Relevance
“…Additionally, most published studies have several major drawbacks that hinder study replication (e.g. provision of limited description of the methodology utilized; utilize an undeterminable number of cells; do not provide detailed semen parameters or detailed information regarding the topological organization of targeted regions within sperm) 35 37 38 43 53 . Telomeres are important features of chromosomes conferring stability, genome integrity, and possess crucial biological features (e.g., length) for human reproduction 54 55 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most published studies have several major drawbacks that hinder study replication (e.g. provision of limited description of the methodology utilized; utilize an undeterminable number of cells; do not provide detailed semen parameters or detailed information regarding the topological organization of targeted regions within sperm) 35 37 38 43 53 . Telomeres are important features of chromosomes conferring stability, genome integrity, and possess crucial biological features (e.g., length) for human reproduction 54 55 56 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that multiple chromocentres are a prominent feature of the aberrant spermatid nuclei44. In addition, in immotile spermatozoa chromocenter formation is disrupted21. Whether multiple chromocenteres are the result of a centromeric heterochromatin spreading or the result of a failure of the centromeres to coalesce into one area remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have described the changes in the sperm cell chromosomes topology in men with reproductive failures and the correct somatic karyotype212223242526. The observed disorders in spermatozoa from males with idiopathic infertility have been ascribed to (1) atypical packaging of chromosomal territories, (2) instability of chromosomes topology and (3) a lack of interaction between the telomeres.…”
mentioning
confidence: 99%
“…Furthermore, in the last year, several publications include the methodology for obtaining kinetic data from fish semen with the ImageJ-CASA system [20] [21]. Part of these developments is marked by the use of automatic systems to describe the quality of the semen samples (for example, analysis of the percentage of chromocenter in the sperm cell nucleus), and make a correlation with quality and motility of semen sample [3] or in human spermatozoa for study flow cytometry [2].…”
Section: Discussionmentioning
confidence: 99%
“…Sperm cells are complex models, and the study of their motility is necessary in order to describe the quality of the samples [1], which is important in the fertilization process as faster and quantitative analysis help to identify the best sample; in recent years, computational systems have been used to measure the quality of human spermatozoa [2], and for following morphological changes [3]. Semen is manipulated in vitro at the industrial level in order to improve production.…”
Section: Introductionmentioning
confidence: 99%